2023
DOI: 10.1186/s12905-023-02692-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of neutrophil to lymphocyte ratio in endometriosis: a systematic review and meta-analysis

Fatemeh Tabatabaei,
Hossein Tahernia,
Arshin Ghaedi
et al.

Abstract: Background The purpose of this systematic review and meta-analysis was to compile existing evidence on the significance of the NLR in predicting endometriosis in order to aid clinical decision-making and outcomes. Methods We searched ProQuest, Web of Science, and PubMed for related studies published before January 2, 2023. Standardized mean difference (SMD) with a 95% confidence interval (CI) was reported for each outcome. Because a significant lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…NLR is a commonly employed inflammatory marker in blood, serving as a diagnostic and prognostic indicator for a range of medical conditions. [46][47][48] Recent research has highlighted the diagnostic and prognostic significance of NLR in different types of cancerous tumors. [49][50][51][52] Investigations into gynecologic malignancies have revealed that a high NLR is correlated with unfavorable clinical outcomes in ovarian, endometrial, and cervical cancers, as well as uterine sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…NLR is a commonly employed inflammatory marker in blood, serving as a diagnostic and prognostic indicator for a range of medical conditions. [46][47][48] Recent research has highlighted the diagnostic and prognostic significance of NLR in different types of cancerous tumors. [49][50][51][52] Investigations into gynecologic malignancies have revealed that a high NLR is correlated with unfavorable clinical outcomes in ovarian, endometrial, and cervical cancers, as well as uterine sarcoma.…”
Section: Discussionmentioning
confidence: 99%